(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Pyometra is a condition characterized by the accumulation of pus within the uterine cavity that usually develops in elderly women . Spontaneous rupture of pyometra causing diffuse peritonitis is very rare.Unless recognized in time it can be a life threatening condition. The aim of this article is to report a case of spontaneous rupture of pyometra who was admitted in our hospital as surgical emergency and was successfully treated by surgery. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 48-51